PU white primer for artificial stone bathtub

By using nano-silicon modified polymers and other modified materials in PU white primer, the existing PU white primer has been solved, and the problems of insufficient adhesion and poor heat water resistance in artificial stone bathtub applications have been achieved, thus achieving excellent adhesion Focus, hardness and high and low temperature difference resistance improve the quality and service life of the coating.

CN119463700APending Publication Date: 2025-02-18SHANGHAI ZHANCHEN COATING CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411682938.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing PU white primer has problems such as insufficient adhesion, poor heat and water resistance, and poor cold and heat resistance in artificial stone bathtub applications, resulting in low coating quality and short service life.

Method used

Nanosilicon modified polymer is used as the main film-forming substance, combined with castor oil alkyd resin, glass powder, talc powder and HDI isocyanurate curing agent, optimize raw material ratio, improve adhesion, hardness and high and low temperature difference resistance .

Benefits of technology

It significantly improves the adhesion, hardness and high and low temperature difference resistance of PU white primer, ensures the quality and service life of the coating, and meets the requirements of high-end application scenarios such as artificial stone bathtubs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005148810280000051
    Figure BDA0005148810280000051
  • Figure BDA0005148810280000061
    Figure BDA0005148810280000061
  • Figure BDA0005148810280000062
    Figure BDA0005148810280000062
Patent Text Reader

Abstract

The invention discloses a PU white primer for an artificial stone bathtub. The PU white primer is prepared by blending a main agent, a curing agent and a diluent according to the mass ratio of 100: (49-51): (25-35), the main agent comprises 40%-50% of a nano silicon modified polymer, 5%-10% of castor oil alkyd resin, 3%-7% of a viscosity adjusting diluent, 0.1%-0.3% of a defoaming agent, 0.5%-1% of a dispersing agent, 3%-5% of an anti-settling agent, 15%-25% of titanium dioxide, 10%-25% of glass powder and 5%-10% of talcum powder; the curing agent is prepared from 55.0 percent to 75.0 percent of HDI (Hexamethylene Diisocyanate) isocyanurate and 25.0 percent to 45.0 percent of butyl acetate; the diluent comprises the following components in percentage by weight: 60.0%-70.0% of butyl acetate, 15.0%-20.0% of ethyl acetate and 15.0%-25.0% of propylene glycol methyl ether acetate. The white primer has excellent hot water resistance, high-low temperature difference resistance, excellent adhesive force and relatively high hardness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of polyurethane paints, and specifically relates to a PU white primer for an artificial stone bathtub and a preparation method thereof. Background Art

[0002] As people's living standards improve, the demand for artificial stone bathtubs is increasing. The surface coating of artificial stone bathtubs needs to have excellent adhesion, excellent water resistance and high temperature resistance. However, although there are many types of primers on the market, special primers specifically for artificial stone bathtubs are relatively scarce. Existing primer products generally have problems such as insufficient adhesion, poor hot water resistance, and unsatisfactory resistance to cold and hot temperature differences during use. Some products even have quality problems such as cracking, bubbling, and paint peeling. Therefore, it has become an urgent need in the current field of coating technology to develop a PU white primer (i.e., polyurethane white primer) with good adhesion, excellent hot water resistance, good resistance to cold and hot temperature differences, high hardness and superior comprehensive performance to solve these problems.

[0003] Patent document CN118931337A discloses a nano-silicon modified resin coating, comprising the following raw material components: 100 parts of nano-silicon modified alkyd resin, 1-1.4 parts of composite drying agent, 25-30 parts of composite powder filler, 40-45 parts of xylene, 0.6-1 parts of dispersant, 0.4-0.7 parts of defoamer and 0.3-0.5 parts of anti-skinning agent; the nano-silicon modified alkyd resin is prepared by ultrasonic mixing of organic nano-silicon and alkyd resin in a mass ratio of 1: (40-45). However, the core goal of this document is to improve the drying rate and glossiness of the coating film. The nano-silicon modified alkyd resin used is modified by uniformly dispersing organic nano-silicon in alkyd resin. Although it can reduce the viscosity of alkyd resin, enhance its fluidity, fill minor defects, improve glossiness, adjust surface tension, and accelerate the curing and drying process of the coating; however, this document does not show significant advantages or effects in terms of hot water resistance, high and low temperature resistance and adhesion performance.

[0004] Patent document CN109749614A discloses a polyurethane odorless white primer and its preparation method, which includes by weight: 30-40 parts of alkyd odorless resin, 14-18 parts of functional filler, 10-18 parts of titanium dioxide, 14-18 parts of talcum powder, 1.5-2.5 parts of anti-settling agent, 1.0-2.0 parts of organic bentonite, 0.6-1.0 parts of dispersant, 0.3-0.5 parts of leveling agent, 0.2-0.5 parts of defoamer, 0.1-0.3 parts of anti-skinning agent, and 3-10 parts of solvent. However, the white primer of the document mainly uses alkyd resin as the main film-forming material. Compared with nano silicone resin, alkyd resin is significantly insufficient in key performance indicators such as water resistance, heat resistance and hardness. Therefore, the polyurethane odorless white primer mentioned in the document cannot meet the high standard requirements of artificial stone bathtubs for primers, especially in terms of adhesion, hot water resistance, resistance to cold and hot temperature differences, and high hardness. These performance deficiencies limit the applicability of this primer in high-end application scenarios such as artificial stone bathtubs. Summary of the invention

[0005] The purpose of the present invention is to provide a PU white primer for an artificial stone bathtub and a preparation method thereof. The PU white primer not only exhibits excellent adhesion, good hot water resistance and high and low temperature resistance, but also has high paint film hardness, effectively ensuring the quality and service life of the coating, and can solve the technical problems existing in the application of existing PU white primer in artificial stone bathtubs.

[0006] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0007] The PU white primer for an artificial stone bathtub of the present invention is prepared by mixing a main agent, a curing agent and a diluent in a mass ratio of 100: (49-51): (25-35); the characteristic is that:

[0008] The main agent comprises the following components by mass fraction: 40% to 50% of nano-silicon modified polymer, 5% to 10% of castor oil alkyd resin, 3% to 7% of viscosity adjusting diluent, 0.1% to 0.3% of defoaming agent, 0.5% to 1% of dispersant, 3% to 5% of anti-settling agent, 15% to 25% of titanium dioxide, 10% to 25% of glass powder, and 5% to 10% of talc;

[0009] The curing agent comprises the following components by mass fraction: 55.0% to 75.0% of HDI isocyanurate and 25.0% to 45.0% of butyl acetate;

[0010] The diluent comprises the following components by mass fraction: 60.0% to 70.0% of butyl acetate, 15.0% to 20.0% of ethyl acetate, and 15.0% to 25.0% of propylene glycol methyl ether acetate;

[0011] The nano-silicon modified polymer is a polymer synthesized by reaction of phenylchlorosilane, methylchlorosilane and special silane monomer as main raw materials, with a number average molecular weight of 1200-2100, a viscosity of 30-40s after applying 4 cups at 25°C, and a solid content of 100%; for example, Lencolo8780 self-drying nano-silicon varnishing agent of Guangdong Lancolu New Materials Co., Ltd.;

[0012] The castor oil alkyd resin is made from castor oil, synthetic fatty acids, polyacids and polyols as main raw materials through transesterification and gradual polycondensation, and has a number average molecular weight of 3000 to 4000, such as the brand JD16-70D produced by Shanghai Zhanchen Paint Co., Ltd.;

[0013] The viscosity adjusting diluent is at least one of butyl acetate, ethyl acetate, and propylene glycol methyl ether acetate;

[0014] The defoamer is at least one of a foam-breaking polymer or a polysiloxane solution, such as a polysiloxane solution with a brand number of BYK066 from BYK Chemical Company;

[0015] The dispersant is modified polyurethane, purchased from EFKA's EFKA-4010 dispersant; the anti-settling agent is a dispersion of polyamide wax expansion particles, such as 6900-HV polyamide wax thixotropic agent from Desbaron; the titanium dioxide is rutile titanium dioxide, such as R-906 from Shanghai Yantai Industrial Co., Ltd. and CR510 from Jinzhou Titanium Industry Co., Ltd.;

[0016] The average particle size of the glass powder is: 4.5±0.5um, for example, the brand of Foshan Housheng Chemical Co., Ltd. is JH-10; the talc powder is 1250 mesh talc powder, for example, the brand of Jiangmen Guiguang Chemical Co., Ltd. is 1250 mesh talc powder;

[0017] The HDI isocyanurate is a hexamethylene diisocyanate-based polyisocyanate (or HDI trimer), with a CAS number of 28182-81-2, such as WANNATE HT-100 from Wanhua Chemical;

[0018] The CAS number of the propylene glycol methyl ether acetate is 108-65-6, and it is a conventional product available on the market.

[0019] The preparation method of the PU white primer for artificial stone bathtubs of the present invention comprises the following steps: respectively stirring the main agent, curing agent and diluent according to their respective raw material ratios and uniformly mixing and stirring the three before use, and then construction can be carried out, and the construction method is a conventional method in the art.

[0020] The PU white primer for an artificial stone bathtub of the present invention is applied to the coating of the surface of the artificial stone bathtub, and is also applicable to the primer coating of the surface of stone and wood with special requirements on hot water resistance, high and low temperature resistance and hardness in bathrooms, kitchens and the like.

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] The present invention uses nano-silicon modified polymer as the main film-forming substance, which can significantly improve the adhesion, hardness and high and low temperature difference resistance of the product, adds a small amount of castor oil alkyd resin to improve flexibility, glass powder is used to improve filling and hardness, and talcum powder is used to improve product filling and polishing properties; HDI isocyanurate curing agent provides cross-linking reaction curing and flexibility, and the optimized raw material ratio ensures that the white primer has excellent hot water resistance, high and low temperature difference resistance, excellent adhesion and high hardness. DETAILED DESCRIPTION

[0023] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application clearer, the present application is further described in detail in conjunction with the embodiments below. It should be noted that the embodiments of the present invention are only for explaining the contents of the present application and do not constitute a limitation on the technical solutions of the present application. If no specific conditions are specified in the specific implementation method, it shall be carried out according to conventional conditions or conditions recommended by the manufacturer.

[0024] Examples 1 to 3

[0025] The mass fractions of the raw materials and components of the PU white primers of Examples 1 to 3 and Comparative Examples 1 to 2 are listed in Table 1. The preparation method comprises the following steps:

[0026] (1) Main agent: Add nano-silicon modified polymer Lenclol 8780 and castor oil alkyd resin JD16-70 into a stirring container, add anti-settling agent 6900-HV, dispersant EFKA4010 and defoamer BYK066 in sequence under low speed (500 rpm) stirring, and then change to medium speed (1000 rpm) stirring and dispersing for 5 minutes; slowly add titanium dioxide R-906, glass powder JH-10 and 1250 mesh talcum powder in sequence under low speed (500 rpm) stirring, and disperse at high speed (1500 rpm) for 20 to 25 minutes. When the fineness is ≤45 μm, add butyl acetate at low speed (500 rpm) and stir well.

[0027] (2) Stir and mix the curing agent and diluent according to their respective proportions.

[0028] (3) Mix the main agent, curing agent and diluent in a mass ratio of 100:50:30 and stir evenly, then you can start construction; Construction method: manual spraying.

[0029] Table 1 Mass fractions of raw materials and components of Examples 1 to 3 and Comparative Examples 1 to 2, unit: %

[0030]

[0031]

[0032] Note: * refers to mixed fatty acid type alkyd resin.

[0033] Comparative Example 1 is a comparative example of Example 1, except that, in Comparative Example 1, 40% of the nano-silicon modified polymer in the main agent is replaced with an equal weight of mixed fatty acid type alkyd resin (JD1158-70 produced by Shanghai Zhanchen Paint Co., Ltd.), and the remaining raw materials and preparation methods are the same as those in Example 1.

[0034] Comparative Example 1 is a comparative example of Example 2, except that, in Comparative Example 2, 50% of the nano-silicon modified polymer and 6% of the castor oil alkyd resin in the main agent are replaced with an equal weight of hydroxy acrylic resin (AC1151B produced by Tongde Chemical Company), and the remaining raw materials and preparation methods are the same as those in Example 2.

[0035] Test experiment example

[0036] The PU white primers of Examples 1 to 3 and Comparative Examples 1 to 2 were subjected to appearance tests, and performance tests were performed in accordance with GB / T4893 "Physical and Chemical Properties of Furniture Surface Paint Films Test", GB 18581-2020 "Limits of Hazardous Substances in Wood Coatings" and GB / T 23997-2009 "Solvent-based Polyurethane Wood Coatings for Interior Decoration and Renovation". The results are shown in Table 2.

[0037] Table 2 Performance test results of Examples 1 to 3 and Comparative Examples 1 to 2

[0038]

[0039]

[0040] As can be seen from Table 2, the PU white base of Examples 1 to 3 has the advantages of excellent adhesion, dry heat resistance, wet heat resistance, resistance to cold and hot temperature difference and high hardness, and various indicators are better than those of the comparative example, and the harmful substance limit indicators also meet the national standards.

[0041] According to the requirements of the customers of the artificial stone bathtub manufacturer, the artificial stone bathtub was used as the substrate, and the PU white primer of Examples 1 to 3 and Comparative Examples 1 to 2 was sprayed, and the performance of the paint film was tested. The adhesion was tested according to the GB / T4893.4-2023 standard, the pencil hardness was tested according to the GB / T 6739-2022 standard, the liquid resistance was tested according to the GB / T 4893.1-2021 standard, the resistance to cold and hot temperature difference was tested according to the GB / T4893.7-2013 standard, the resistance to moisture and heat was tested according to the GB / T 4893.2-2020 standard, and the resistance to hot water bath was tested according to the method required by the customer; the results are shown in Table 3.

[0042] Table 3 Performance comparison of Examples 1 to 3 and Comparative Examples 1 to 2

[0043]

[0044] As can be seen from Table 3, Examples 1 to 3 have excellent performance in terms of resistance to cold and hot temperature differences, which are significantly better than Comparative Examples 1 to 2; especially in the adhesion evaluation after the cold and hot temperature difference test, Examples 1 to 3 show excellent performance of 0-1, while Comparative Examples 1 to 2 are only 3-4, with a significant difference; in other key performance indicators such as pencil hardness, liquid resistance and wet heat resistance, Examples 1 to 3 also show obvious advantages over Comparative Examples 1 to 2. Regarding the hot water bath resistance that customers are particularly concerned about, Examples 1 to 3 did not show common defects such as bubbling and gloss loss in the test, while Comparative Examples 1 to 2 generally showed bubbling and other problems.

[0045] Based on the above test data, Examples 1 to 3 fully meet the high standard requirements of the artificial stone bathtub for the paint film, including excellent adhesion, excellent hot water resistance, good high and low temperature resistance and high hardness, proving its feasibility and reliability in practical applications.

Claims

1. A PU white primer for an artificial stone bathtub, which is prepared by mixing a main agent, a curing agent and a diluent in a mass ratio of 100: (49-51): (25-35); characterized in that: The main agent includes the following components by mass fraction: 40% to 50% of nano-silicon modified polymer, 5% to 10% of castor oil alkyd resin, 3% to 7% of viscosity regulating diluent, 0.1% to 0.3% of defoaming agent, 0.5% to 1% of dispersant, 3% to 5% of anti-settling agent, 15% to 25% of titanium dioxide, 10% to 25% of glass powder, and 5% to 10% of talc; The curing agent includes the following components by mass fraction: 55.0% to 75.0% of HDI isocyanurate and 25.0% to 45.0% of butyl acetate; The diluent comprises the following components in mass fractions: 60.0% to 70.0% of butyl acetate, 15.0% to 20.0% of ethyl acetate, and 15.0% to 25.0% of propylene glycol methyl ether acetate.

2. The PU white primer for artificial stone bathtub according to claim 1, characterized in that: The nano-silicon modified polymer is a polymer synthesized by reaction using phenylchlorosilane, methylchlorosilane and special silane monomers as main raw materials, with a number average molecular weight of 1200-2100, a 4-cup coating viscosity of 30-40s at 25°C, and a solid content of 100%.

3. The PU white primer for artificial stone bathtub according to claim 1, characterized in that: The castor oil alkyd resin is prepared by using castor oil, synthetic fatty acid, polyacid and polyol as main raw materials through ester exchange and gradual polycondensation, and has a number average molecular weight of 3000-4000.

4. The PU white primer for artificial stone bathtub according to claim 1, characterized in that: The viscosity adjusting diluent is at least one of butyl acetate, ethyl acetate and propylene glycol methyl ether acetate.

5. The PU white primer for artificial stone bathtub according to claim 1, characterized in that: The defoamer is at least one of a foam-breaking polymer or a polysiloxane solution; The dispersant is modified polyurethane, EFKA-4010 dispersant purchased from Efka; the anti-settling agent is a dispersion of polyamide wax expanded particles, such as 6900-HV polyamide wax thixotropic agent from Despalon; the titanium dioxide is rutile titanium dioxide, such as R-906 from Shanghai Yantai Industrial Co., Ltd. and CR510 from Jinzhou Titanium Industry Co., Ltd.

6. The PU white primer for artificial stone bathtub according to claim 1, characterized in that: The average particle size of the glass powder is 4.5±0.5um; the talcum powder is 1250 mesh talcum powder.

7. The PU white primer for artificial stone bathtub according to claim 1, characterized in that: The HDI isocyanurate is a hexamethylene diisocyanate-based polyisocyanate.

8. The method for preparing a PU white primer for an artificial stone bathtub according to any one of claims 1 to 7, comprising the following steps: stirring the main agent, curing agent and diluent respectively according to their respective raw material ratios; mixing and stirring the three before use, and then construction can be carried out, and the construction method is a conventional method in the field.

9. The PU white primer for artificial stone bathtubs according to any one of claims 1 to 7 is used for coating the surface of artificial stone bathtubs, and is also suitable for primer coating on the surface of stone and wood materials such as bathrooms and kitchens that have special requirements on hot water resistance, high and low temperature resistance and hardness.

Citation Information

Patent Citations

  • Polyurethane odor-removing white primer and preparation method thereof

    CN109749614A

  • Nano silicon modified resin coating and preparation method thereof

    CN118931337A

  • Impregnating encapsulation material with excellent coating withstand voltage, and preparation method thereof

    CN108300212A

  • High-temperature-resistant ink-jet printing paint and preparation method thereof

    CN114874696A

  • High-flexibility PU spraying white primer

    CN116042082A